AN ANALYTICAL STUDY OF NIRVANA IN THERAVADA BUDDHISM - มงคลทอง, พระครูปลัดไพศาล; Phra Suphachai Sutthiratano (Tokaew) (Journal of Contemporary Buddhist Society = JCBS, 2024)
This academic article have a purpose For the study of the study and analysis of Nirvana in Theravada Buddhism. From the study, it was found that Nirvana is the ultimate goal of the principle. Buddhist Dhamma Practices which has roots from the Pali language and Sanskrit When referring to the meaning of the Sutta, there are 2 main groups of Nirvana as a whole: Nirvana that still has the five aggregates remaining, and Nirvana that has extinguished all the aggregates and only the Dhamma aggregate remains. from controversial issues Same thing about nirvana as ego. or Anattā, the Buddha never explained that an Arahant who has attained Nirvana When the Khan is extinguished What condition will it be in? An explanation can be done in the form of Nirvana, which is the cessation of suffering, the cessation of desire, like a fire that has been extinguished until it is no longer able to flare up again. for the arhat After passing away, the Buddha did not confirm existence or extinction. He only said that when he passed away, both gods and humans would no longer be able to see him, which is controversial. About the state of nirvana It has been around for thousands of years, so it can be divided into two groups to discuss the overall picture, as well as the types of Nirvana. This is a group that believes that nirvana is a state of perpetuity, happiness, and ego. This group believes that with the idea that The state of Nirvana It must be contrary to the Three Laws (anicca, dukkha, anattā) according to the principles of Anattalakkhaṇa Sutta and Sunyata (emptiness).